2014
DOI: 10.1007/s40615-014-0054-y
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for Psychotherapy and Illness Beliefs in Turkish Immigrant Inpatients in Germany: Results of a Cultural Comparison Study

Abstract: Objective Some immigrant populations, for instance, Turkish immigrants, suffer from worse mental health than the general population. Moreover, psychotherapeutic treatment does not work well in this group. This might be explained by lower motivation for psychotherapy and particular illness beliefs as important early predictors of treatment outcome. We investigate differences in these predictors between Turkish immigrant inpatients and inpatients without a migration background and evaluate whether particular ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 66 publications
(62 reference statements)
0
26
0
2
Order By: Relevance
“…Two matched inpatient samples (Turkish immigrants vs. Germans without a migration background, n = 50 each) were recruited in five psychiatric clinics in 2011 and 2012 [ 38 ]. Participants were asked about subjective concepts of mental illness, motivation for psychotherapy, and mental health symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Two matched inpatient samples (Turkish immigrants vs. Germans without a migration background, n = 50 each) were recruited in five psychiatric clinics in 2011 and 2012 [ 38 ]. Participants were asked about subjective concepts of mental illness, motivation for psychotherapy, and mental health symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…An ethnopsychological study showed that Albanian-speaking immigrants in Switzerland understood their suffering as part of normal life, given by god or fate (fati), and something that cannot be cured but has to be borne with endurance (durim) (Shala et al, 2019). Fatalism was also found among Turkish immigrants in Germany (Franz et al, 2007;Reich, Bockel, & Mewes, 2015). When compared to German patients, Turkish immigrants showed more fatalistic-external control attributions for mental distress, which resulted in lower motivation for psychotherapy.…”
Section: Cultural Concepts Of Distressmentioning
confidence: 99%
“…). Also, Turkish-German psychiatric inpatients, compared to natives, expected to assume a mainly passive role during psychotherapy and to benefit more from pharmacological treatment (Reich et al, 2015). Furthermore, a Dutch study found that Turkish-Dutch individuals more often experienced general discordance between their perceived care need and the care they received than natives did, which was partly explained by baseline symptom differences (Fassaert et al, 2009).…”
Section: Obstacles and Facilitators For Treatment Accessibility And Tmentioning
confidence: 99%